Improvement of Food Packaging-Related Properties of Whey Protein Isolate-Based Nanocomposite Films and Coatings by Addition of Montmorillonite Nanoplatelets - Schmid, Markus; Merzbacher, Sarah; Brzoska, Nicola; Müller, Kerstin; Jesdinszki, Marius (Frontiers in Materials, 2017)
In this study, the effects of the addition of montmorillonite (MMT) nanoplatelets on whey protein isolate (WPI)-based nanocomposite films and coatings were investigated. The main objective was the development of WPI-based MMT nanocomposites with enhanced barrier and mechanical properties. WPI-based nanocomposite cast films and coatings were prepared by dispersing 0% (reference sample), 3, 6, 9% (w/w protein) MMT, or, depending on the protein concentration, also 12 and 15% (w/w protein) MMT into native WPI-based dispersions, followed by subsequent denaturation during the drying and curing process. The natural MMT nanofillers could be randomly dispersed into film-forming WPI-based nanodispersions, displaying good compatibility with the hydrophilic biopolymer matrix. As a result, by addition of 15% (w/w protein) MMT into 10% (w/w dispersion) WPI-based cast films or coatings, the oxygen permeability (OP) was reduced by 91% for glycerol-plasticized and 84% for sorbitol-plasticized coatings, water vapor transmission rate was reduced by 58% for sorbitol-plasticized cast films. Due to the addition of MMT nanofillers, the Young’s modulus and tensile strength improved by 315 and 129%, respectively, whereas elongation at break declined by 77% for glycerol-plasticized cast films. In addition, comparison of plasticizer type revealed that sorbitol-plasticized cast films were generally stiffer and stronger, but less flexible compared glycerol-plasticized cast films. Viscosity measurements demonstrated good processability and suitability for up-scaled industrial processes of native WPI-based nanocomposite dispersions, even at high-nanofiller loadings. These results suggest that the addition of natural MMT nanofillers into native WPI-based matrices to form nanocomposite films and coatings holds great potential to replace well-established, fossil-based packaging materials for at least certain applications such as oxygen barriers as part of multilayer flexible packaging films.